MODEL PENINGKATAN KINERJA SDM BERBASIS HUMAN CAPITAL - Rizal Fahmi Bachtiar; Widodo Widodo (Jurnal Ekonomi dan Bisnis, 2016)
This study aimed to analyze the influence of education and work experience through humancapital on the performance of human resources in an organization. A discussion of the importanceof education, work experience, and human capital to improve HR performance has been widelydiscussed in some literature review. Although a lot of other factors that affect the performanceof HR, this study only discusses about the existence of education, work experience, and humancapital as a determinant of human performance. Data obtained from 75 respondents by usingquestionnaire. Data analysis using SPSS 16 shows that the performance of HR in organizationscan be improved by taking into account the level of education and work experience through thehuman capital of the organization’s human resources. Education and work experience throughhuman capital has a positive and significant effect on the performance of human resources.Keywords: education, work experience, human capital and HR performance